Analysis of Fluid Intake During Pregnancy - Dilaver, Irem; Parlak Somuncu, Busra; Topbas, Murat; Sahin, Kubra; Ustundag, Medine Gozde; Agrali Gundogmus, Cansu; Can, Gamze; Beyhun, Nazim Ercument (Makara Journal of Health Research, 2024)
Background: Pregnancy is an important process that affects the body’s daily water requirements through various mechanisms. Adequate fluid intake also plays a critical role in pregnancy. This research aimed to determine levels of water/fluid intake and influencing factors among pregnant women presenting to a university hospital in Trabzon, Türkiye. Methods: A total of 1,082 pregnant women were included in this cross-sectional research. A questionnaire was used during the face-to-face interviews to collect data. SPSS version 23.0 software was employed during data analysis, and logistic regression was applied to identify factors that affect adequate daily fluid intake. Results: The pregnant women in this study consumed a daily mean amount of water amounting to 1.8 ± 0.9 liters and had a mean fluid intake of 2.3 ± 0.9 liters. Results showed that daily fluid intake was inadequate in 557 (51.5%) participants. At the same time, logistic regression analysis revealed higher rates of sufficient daily fluid intake among pregnant women who were informed about water intake by their physicians and women with higher total monthly household incomes. Conclusions: Fluid intake was lower than the recommended amount for pregnant women in approximately half of the study’s participants. High levels of education, household income, and information about water intake provided by a physician were identified as important factors related to adequate daily fluid intake.